Study on the kinetics and influence of feline platelet aggregation and deaggregation. Issue 1 (December 2015) - Riond, Barbara; Waßmuth, Andrea; Hartnack, Sonja; Hofmann-Lehmann, Regina; Lutz, Hans
Abstract Background Feline platelets are prone to clumping after blood collection, rendering the determination of accurate platelet counts difficult for clinical laboratories and resulting in a high incidence of pseudothrombocytopenia in feline haematology reports. No information is available about the kinetics of platelet aggregate formation in feline ethylenediaminetetraacetic acid blood and the course of platelet counts over a clinically relevant time period. The aim of the present study was to determine platelet counts in healthy cats over a time period of 24 h after blood collection at 9 time points; to assess potential effects of platelet aggregates, anaesthesia and bleeding conditions on feline platelets and white blood cell counts; and finally, to investigate if glucose concentration is associated with the presence of aggregates. From 30 clinically healthy cats, blood samples were analysed at 9 different time points using two different haematology instruments (using fluorescence and impedance-based flow cytometry) in the counting chamber and by blood smear evaluation. Results Fourteen of the 30 samples were thrombocytopenic at one to 8 time points after collection as analysed on a fluorescence flow cytometry haematology analyser. At the 24-h timepoint, all thrombocytopenic samples had returned to normal platelet counts. Seventeen of the 30 samples showed platelet aggregates in the counting chamber. Significant differences in platelet counts were associated with the presence and size of aggregates and time since bleeding. No statistically significant differences in counts were found with regard to the quality of blood collection or the use of anaesthesia. Platelet aggregation and, therefore, pseudothrombocytopenia occurred in 57 % of the investigated samples at different time points. Conclusion For the first time, deaggregation of feline platelet aggregates could be demonstrated as a reversible effect of platelet aggregation. For clinical laboratories or veterinarians, it may be helpful to rerun feline samples with pseudothrombocytopenia to obtain a more reliable platelet count. The quality of blood collection seems not to be causative for platelet aggregation. Blood smear evaluation is absolutely indicated in cases when haematology instruments give PLT counts below the reference interval.